Water and Society 2013
DOI: 10.2495/ws130171
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen removal options: emphasizing SOLDIS for the filtrate of a GSAP Microflush toilet

Abstract: The Microflush toilet system, a low-flush off-grid macro-organism enhanced aerobic digester has been prototyped and shown to be an effective toilet solution for rural communities in the tropical developing world. The system rapidly filters solids in the waste stream from liquids-urine and greywater from hand washing. The solids are digested and vermi-composted with e. fetida and other macro-organisms resulting in high mass reduction and pathogen removal. The resulting compost is harvested every 2-3 years. Succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The ability of the GSAP Microflush toilet to process waste is supported by previous studies investigating temperature distribution within the digester (Mecca et al, 2017) and the use of SODIS for pathogen reduction in liquid effluent (Mecca et al, 2013b). In addition, studies of vermicomposting as a waste treatment method have demonstrated the effectiveness of this approach for mass reduction and pathogen removal (Hill and Baldwin, 2012;Soobhany et al, 2017).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 80%
See 1 more Smart Citation
“…The ability of the GSAP Microflush toilet to process waste is supported by previous studies investigating temperature distribution within the digester (Mecca et al, 2017) and the use of SODIS for pathogen reduction in liquid effluent (Mecca et al, 2013b). In addition, studies of vermicomposting as a waste treatment method have demonstrated the effectiveness of this approach for mass reduction and pathogen removal (Hill and Baldwin, 2012;Soobhany et al, 2017).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 80%
“…The genera and unclassified OTUs that were abundant in the untreated liquid effluent were greatly reduced or not detected in the SSF-treated effluent; however, these taxa increased in abundance in the SODIS-treated effluent. A previous study of SODIS for application with the GSAP Microflush toilet system showed significant reduction of viable E. coli over eight hours of exposure to sunlight (Mecca et al, 2013b). Given this and other studies showing the capacity of SODIS to sanitize contaminated water (Boyle et al, 2008;Caslake et al, 2004), it is possible that PeerJ reviewing PDF | (2018:09:31004:1:0:NEW 31 Oct 2018)…”
Section: Discussionmentioning
confidence: 94%
“…The ability of the GSAP Microflush toilet to process waste is supported by previous studies investigating temperature distribution within the digester (Mecca, Stifler & Beley, 2017) and the use of SODIS for pathogen reduction in liquid effluent (Mecca, Pellock & Bretz, 2013b). In addition, studies of vermicomposting as a waste treatment method have demonstrated the effectiveness of this approach for mass reduction and pathogen removal (Hill & Baldwin, 2012; Soobhany, Mohee & Garg, 2017).…”
Section: Introductionmentioning
confidence: 76%
“…Water purification in the WASH+E system is accomplished with a combination of slow sand filtering (SSF) and SODIS. The effectiveness of the latter has been modeled, measured and reported [4]. In all of the WASH+E interventions the emphasis is on effectiveness and cost.…”
Section: A Potable Water Purification Systemmentioning
confidence: 99%